Synthesis, characterization and filtration of adsorptive biobased membrane from Jatropha oil modified with graphene oxide - Harun, Nur Haninah (2022)
Industrial discharges containing heavy metals are one of the major concerns globally. Among various method in water treatment, membrane filtration is favored due to its minimal impact on the environment. To move towards green economy, vegetable oil derivatives have been used as a bio-based polymer due to their chemical properties, sustainability, low cost, and ease of access. Therefore, the purpose of this study is to utilize vegetable oil from Jatropha curcas that is chemically ideal for bio-based membrane synthesis and a droughtresistance plant, hence is easier to sustain. However, due to the common limitation in organic membrane (e.g., low in hydrophilicity, thermal resistance, separation efficiency), this work aims to develop a new bio-based adsorptive membrane filter from Jatropha oil derivatives modified with graphene oxide (GO) to improve its features and performance. Jatropha oil-based polyol (JOL) was mixed with hexamethylene diisocyanate (HDI) to produce Jatropha polyurethane (JPU) in different conditions (HDI:JOL ratio, cross-linking and curing temperature). HDI: JOL ratio was optimum at 5:5 (v/v) with cross-linking and curing temperature at 90 °C and 150 °C, respectively. GO was added into JPU polymer matrix at different weight percent (0.35 wt%, 0.50 wt%, and 0.65 wt%) to form Jatropha/graphene oxide membrane (JPU/GO). JPU and JPU/GO were evaluated and characterized. Glass transition temperature (Tg) and onset temperature (To) were increased from 58°C to 69°C and from 170°C to 202°C, respectively due to the presence of GO that promotes crystallization, thus improve thermal stability. Additionally, contact angle decreased from 88.8° to 52.1°, which signifies higher hydrophilicity due to GO oxygenated functionalities that assist in absorbing water. Besides, JPU/GO 0.50wt% demonstrates higher water flux followed by JPU/GO 0.35wt%, JPU/GO 0.65wt%, and JPU at 523 L/m2.h, 406 L/m2.h, 260 L/m2.h, and 233 L/m2.h, respectively. In filtration, JPU/GO exhibited higher Cu(II) rejection followed by JPU/GO 0.35 wt%, JPU/GO 0.65 wt%, and JPU with rejections at 71.60 %, 67.56 %, 63.58 %, and 33.51%, respectively due to the interaction between GO and Cu(II) ions. Besides, JPU/GO 0.50 wt% optimization for Cu(II) ions removal was done using response surface methodology (RSM) by central composite design (CCD). The experiments were done in different factors (60 - 140 ppm, 1.5 - 2.5 bar, pH 3 - 5). Optimum removal of Cu(II) ions was predicted at 116 ppm, 1.5 bar, and pH 3.7 with 87% rejection. The result obtained within 95% of prediction intervals at 80% rejection. Meanwhile, mass transfer mechanism for JPU/GO 0.50wt% was depicted by combined film theory/solution-diffusion (CFSD) and combined film theory/Spiegler-Kedem (CFSK). From the findings, CFSK model exhibited better prediction than CFSD. Additionally, resistance-in-series model was proposed to study the cause of foulant. Fouling JPU/GO 0.50wt% has reduced rejection to 59% with permeate flux at 291 L/m2.h. After backwashing using pure water, the fouling membrane had achieved 67% rejection with flux at 441 L/m2.h. The fouling studies recorded 52% of flux recovery, 20% reversible fouling ratio, and 48% of irreversible fouling. Results showed JPU/GO 0.50 wt% exhibited adsorptive characteristics. In conclusion, JPU/GO 0.50 wt% offers a better membrane physicochemical property and achieves a good quality permeate with minimal pollutant content. Thus, JPU/GO 0.50 wt% was proven to have the potential as an alternative for wastewater treatment.